Effects of the venom of the rhinoceros horned viper (Bitis nasicornis) on blood coagulation, platelet aggregation, and fibrinolysis - MacKay, N. (1970)
The venom of the rhinoceros horned viper (Bitis nasicornis) has been studied in vitro and has been shown to be anticoagulant. This action appeared to be due to an effect on both the extrinsic and intrinsic blood thromboplastin mechanisms. The venom was also proteolytic and in purified caseinolytic systems activated plasminogen, enhanced the activation of plasminogen by streptokinase, and potentiated the action of plasmin. In the euglobulin clot lysis system high concentrations of venom produced inhibition. The crude venom increased platelet adhesiveness but in high concentrations delayed the snowstorm effect in the Chandler's tube system and inhibited platelet adenosine diphosphate reactivity. Passage through carboxymethylcellulose yielded six fractions. One possessed anticoagulant activity, inhibited plasmin, and increased the optical density of platelet-rich plasma. The other five fractions shortened the plasma recalcification time but had no effect on plasmin activity. Four fractions aggregated platelets and enhanced platelet adenosine diphosphate reactivity.